The Influence of Corporate Social Responsibility (CSR) on Corporate Image at Grand Clarion Hotel Macassar - Rita Muis; M. Liga Suryadana (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2019)
CSR is an important issue in ensuring the survival of the business world today. CSR is a form of the company's concern economic, social, and environmental based on three basic principles that include profit, people and planet. The benefits derived from the application of CSR is to increase the reputation or image and add or increase the strength and image of the company, access to capital, maintaining the quality of human resources, and facilitate risk management.This research aims to identify and analyze the implementation of CSR, corporate image and influence the implementation of CSR in the economic, social and environment against corporate image Grand Clarion Hotel Makassar. This study was designed with the form of quantitative and survey method. Types of samples in this study is nonprobability Sampling, ie accidental sampling and convenience sampling, the sampling technique based on coincidence and convenience as many as 70 respondents who are the target communities CSR, employees and society around the hotel at the time of the study and according to the characteristics of the desired sample , Data were analyzed using path analysis.The results showed that (1) the implementation of CSR in the economic, social and environmental dimensions at high category indicating that CSR has been implemented properly by the Grand Clarion Hotel Makassar, (2) a variable image of the company shows the number of 4.05, which means that the company's image in this hotel is very high GCM and (3) the variable implementation of CSR in the economic dimension, the social dimension and environmental dimensions has direct and indirect influence positively significantly to the image of Grand Clarion Hotel Makassar.To create a positive image for the company, it is one thing to do is implement a CSR program both on the economic, social and environmental. Corporate Image is able to provide many benefits to the company so that the necessary efforts to improve its image in the minds of customers. Corporate Image is the company's intangible assets, and CSR is an investment to improve the asset. CSR can create economic, social, and a better environment will enhance the company's image in the eyes of customers.